Exploring the validity of the charged cluster model for chemical vapour deposition diamond growth. - K., G Saw (2004)

(untitled)
Diamond nucleation remains an unsolved problem. Recently the charged cluster model (CCM) was proposed as the nucleation and growth mechanism for low pressure diamond where electric charges produced by gas activation are the nucleation" sites. This paper explores the validity of the CCM by investigating the nucleation and growth of diamond on faceted sapphire substrates.